2010
DOI: 10.1002/jcp.22356
|View full text |Cite
|
Sign up to set email alerts
|

αVβ3 integrin regulates macrophage inflammatory responses via PI3 kinase/Akt‐dependent NF‐κB activation

Abstract: Controlling macrophage responses to pathogenic stimuli is critical for prevention of and recovery from the inflammatory state associated with the pathogenesis of many diseases. The adhesion receptor αVβ3 integrin is thought to be an important receptor that regulates macrophage differentiation and macrophage responses to external signaling, but it has not been previously identified as a contributor to macrophage-related inflammation. Using an in vitro model of human blood monocytes (Mo) and monocyte-derived mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 46 publications
(62 reference statements)
5
86
0
Order By: Relevance
“…In addition, avb3 ligation reduces oxLDL uptake by down-regulating macrophage scavenger protein expression (CD36, SRA), suggesting that avb3 limits macrophage dysfunction in atherosclerosis. 40 However, avb3 signaling also promotes macrophage NF-kB activation and proinflammatory cytokine expression (tumor necrosis factor-a, IL-1b) in cell culture models, 42 although studies of b3-deficient macrophages are conflicting with both positive and negative effects on homing and proinflammatory gene expression described. 43e45 Smooth muscle cell avb3 ligation promotes cell proliferation and migration under several experimental conditions and reduces oxLDL-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, avb3 ligation reduces oxLDL uptake by down-regulating macrophage scavenger protein expression (CD36, SRA), suggesting that avb3 limits macrophage dysfunction in atherosclerosis. 40 However, avb3 signaling also promotes macrophage NF-kB activation and proinflammatory cytokine expression (tumor necrosis factor-a, IL-1b) in cell culture models, 42 although studies of b3-deficient macrophages are conflicting with both positive and negative effects on homing and proinflammatory gene expression described. 43e45 Smooth muscle cell avb3 ligation promotes cell proliferation and migration under several experimental conditions and reduces oxLDL-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…cRGD is a synthetic peptide containing the RGD sequence, which has been shown to compete with adhesive proteins that bind to β 3 -integrin receptors. cRGD peptide abolishes α V β 3 ligation to the extracellular matrix and the effects on the secretion of TNF-α in macrophages and interrupts the subsequent signal transduction upon β 3 -integrin ligation [19,29]. Our experiments showed that autophagy-related proteins were increased, and autophagosomes formed and accumulated in cardiomyocytes in which β 3 -integrin was blocked by cRGD.…”
Section: Discussionmentioning
confidence: 84%
“…The IκB kinase/nuclear factor-κB, mitogen-activated protein kinase and AMP-activated protein kinase pathways activate autophagy [16,17,18], while only the Akt pathway has inhibitory potential. β 3 -Integrin can also activate Akt signaling in macrophages when LPS is added and in isolated cardiomyocytes simulated by H 2 O 2 [19,20]. The focal adhesion complex, which is the downstream signaling component of integrin, directly controls the activation of Akt in response to cell-matrix adhesion [21].…”
Section: Introductionmentioning
confidence: 99%
“…The a v b 3 integrin is expressed on macrophages, migrating smooth muscle cells, and endothelial cells in the vasa vasorum and intraplaque microvasculature of coronary arteries (19). The tripeptide arginine-glycine-aspartic acid (RGD) has a high affinity for integrin a v b 3 and is often used as the primary binding motif in integrin-targeting imaging agents.…”
Section: F-naf: Using Microcalcification As An Imaging Targetmentioning
confidence: 99%